Sex differences in CRT device implantation rates, efficacy, and complications following implantation: protocol for a systematic review and meta-analysis of cohort studies - Dewidar, Omar; Birnie, David; Podinic, Irina; Welch, Vivian; Wells, George A. (Université d'Ottawa | University of Ottawa, 2021)
Abstract Introduction There is abundant evidence for sex differences in the diagnosis, implantation, and outcomes for cardiac resynchronization therapy (CRT) devices. Controversial data suggesting women are less likely to receive the device regardless of the greater benefit. The aim of this review is to assess sex differences in the implantation rate, clinical effectiveness, and safety of patients receiving CRT devices. Methods We will conduct a systematic literature search of MEDLINE, Embase, and Web of Science to identify cohort studies that meet our eligibility criteria. Title and full text screening will be conducted in duplicate independently. Eligible studies report clinical effectiveness or safety of patients receiving CRT device while providing sex-disaggregated data. Implantation rate will be extracted from the baseline characteristics tables of the studies. The effectiveness outcomes include the following: all-cause death, hospitalization, peak oxygen consumption (pVO2), quality of life (QoL), 6-min walk test, NYHA class reduction, LVEF, and heart failure hospitalization. The complication outcomes include the following: contrast-induced nephropathy, pneumothorax, pocket-related hematoma, pericardial tamponade, phrenic nerve stimulation, device infection, death, pulmonary edema, electrical storm, cardiogenic shock, and hypotension requiring resuscitation. Description of included studies will be reported in detail and outcomes will be meta-analyzed and presented using forest plots when feasible. Risk of bias will be assessed using the Newcastle-Ottawa Scale (NOS) by two review authors independently. GRADE approach will be used to assess the certainty of evidence. Discussion The aim of this review is to determine the presence of differences in CRT implantation between women and men as well as differences in clinical effectiveness and safety of CRT after device implantation. Results from this systematic review will provide important insights into sex differences in CRT devices that could contribute to the development of sex-specific recommendations and inform policy. Systematic review registration PROSPERO CRD42020204804